Right to Be Forgotten in Indonesia and Thailand: Human Rights-Based Legal Reform Inspired by Korea, the U.S., and the European Union - Ampuan Situmeang; Lu Sudirman; Ida Bagus Rahmadi Supancana; Nurlaily Nurlaily; Hari Sutra Disemadi (CV. RADJA PUBLIKA, 2026)
The central legal problem of this study lies in the normative inadequacy and weak enforcement construction of the right to be forgotten within the personal data protection regimes of Indonesia and Thailand amid escalating data breaches in Southeast Asia. This research aims to analyze and compare the normative framework governing the right to be forgotten in Indonesia and Thailand with selected global benchmarks, namely the European Union, South Korea, and the United States, in order to formulate ideal legal constructs adaptable to Southeast Asian contexts. This study employs a normative legal research method supported by a comparative legal approach, examining statutory regulations and secondary legal materials from Indonesia, Thailand, the EU (GDPR), South Korea (PIPA), and the United States (CCPA). The findings reveal that although Indonesia’s Personal Data Protection Law and Thailand’s Personal Data Protection Act formally recognize deletion rights, both frameworks remain incomplete due to limited procedural clarity, weak dispute resolution mechanisms, insufficient third-party deletion obligations, and ambiguous safeguards against re-identification risks. In contrast, the EU’s GDPR mandates third-party takedown obligations and imposes severe financial sanctions, South Korea’s PIPA provides strict deletion duties combined with criminal penalties, and the CCPA establishes structured compliance and notification mechanisms. Consequently, strengthening enforcement pathways, clarifying procedural guarantees, and integrating stricter controller obligations are essential for Indonesia and Thailand to ensure effective realization of the right to be forgotten in rapidly expanding digital societies.